Drug-induced cis-regulatory elements in human hepatocytes affect molecular phenotypes associated with adverse reactions - Saki Gotoh-Saito; Ryoko Wada; Tomoe Nishimura; Hideya Kawaji (Nature Communications)
Abstract Genomic variation drives phenotypic diversity, including individual differences in drug response. While coding polymorphisms linked to drug efficacy and adverse reactions are well characterized, the contribution of noncoding regulatory elements remains underexplored. Using CAGE (Cap Analysis of Gene Expression), profiling transcription initiations of mRNAs and enhancer RNAs, we identify candidate cis-regulatory elements (CREs) and assessed their activities simultaneously in HepG2 cells expressing the drug-responsive transcription factor pregnane X receptor (PXR). Comparison with GWAS data reveals strong enrichment of the drug-induced CREs near variants associated with bilirubin and vitamin D levels. Among those bound by PXR in primary hepatocytes, we identify enhancers of UGT1A1, TSKU, and CYP24A1 and functional alleles that alter regulatory activities. We also find that TSKU influences expression of vitamin D-metabolizing enzymes. This study expands the landscape of PXR-mediated regulatory elements and uncovers noncoding variants impacting drug response, providing insights into the genomic basis of adverse drug reactions.